Supply chain stability: A study on the enabling effect of state-owned capital - Runji Guan; Guangsi Zhang; Feifei Han; Xian Chen (PLoS ONE, 2026)
Enhancing the resilience and security of industrial and supply chains is a key initiative to drive high-quality development of the real economy, yet the role of state-owned capital participation in this context remains insufficiently understood. This study empirically investigates how state-owned capital involvement affects the supply chain stability of private enterprises, addressing a significant gap in the literature on state-owned capital’s impact on supply chain management. Drawing on data from Chinese A-share-listed private enterprises spanning 2013–2022, this study adopts an empirical research design grounded in empowerment theory to construct models that assess the effect of state-owned capital participation on supply chain stability. Mechanism tests and heterogeneity analyses are conducted to identify mediating pathways and boundary conditions. The results suggest that state-owned capital participation significantly enhances the supply chain stability of private enterprises. State-owned capital influences private enterprises through two mechanisms: resource enabling and optimization of internal governance structures. Heterogeneity analysis further reveals that the positive effect is more pronounced among private enterprises with weaker bank-enterprise relationships, lower product competitiveness, poorer internal control systems, and higher levels of negative media coverage. By clarifying the stabilizing role of state-owned capital participation in enhancing supply chain stability, this study contributes to both supply chain management theory and the impact of state-owned capital on private enterprises. It also provides policy strategies to strengthen industrial and supply chain resilience and security, while offering actionable insights into targeted policy interventions tailored to different types of private enterprises.